PENGARUH STRATEGI PEMBELAJARAN ARIAS SETTING MODEL PEMBELAJARAN KOOPERATIF TIPE NHT TERHADAP MOTIVASI DAN HASIL BELAJAR BIOLOGI - Dian Safitri; Maryam Maryam; Muhammad Khalifah Mustami (Jurnal Biotek, 2016)
Strategy of ARIAS setting cooperative learning model of NHT type a strategy and learning model has five phases; assurance, relevance, interest, assessment, and stimulation. That’s strategy implemented by setting cooperative learning model NHT. The study aimed at examining (1) learning motivation of Biology of students taught by using ARIAS learning strategies setting cooperative learning model NHT types, (2) learning motivation of Biology of students taught by using ARIAS learning strategies setting direct learning model, (3) students’ learning outcomes of Biology taught by using ARIAS learning strategy of cooperative learning model of NHT type, (4) students’ learning outcomes of Biology taught by using ARIAS learning strategy of direct learning model, (5) the influence of the implementation of ARIAS learning strategies of cooperative learning model of NHT type on students’ learning motivation and students’ learning outcomes of Biology. This study was a quasi-experiment. The population was all of grade IPA students at SMA. Samples were selected by employing purposive sampling technique. The results of study revealed that(1) students’ learning motivation of  Biology in the control class improved with the average score by 12,49; (2) students’ learning motivation of  Biology in the experiment class improved with the average score by by24,93; (3) students’ learning outcomes of  Biology in the control class improved with the average score by 22,44; (4) students’ learning outcomes of  Biology in the experimental class improved with the average score by 35,44; (5) the implementation of ARIAS strategy of cooperative learning model of NHT type gave significant influence toward students' learning motivation and the biology learning outcomes of Biology.